A Molecular Link Between Diabetes and Breast Cancer: Therapeutic Potential of Repurposing Incretin-based Therapies for Breast Cancer - Jaiswal, Pooja; Tripathi, Versha; Nayak, Aakruti; Kataria, Shreya; Lukashevich, Vladimir; Das, Apurba K.; Parmar, Hamendra S. (Current Cancer Drug Targets, 2021)
Female breast cancer recently surpassed lung cancer and became the most commonly diagnosed cancer worldwide. As per the recent data from WHO, breast cancer accounts for one out of every 8 cancer cases diagnosed among an estimated 2.3 million new cancer cases. Breast cancer is the most prevailing cancer type among women causing the highest number of cancer-related mortality. It has been estimated that in 2020, 68,5000 women died due to this disease. Breast cancers have varying degrees of molecular heterogeneity; therefore, they are divided into various molecular clinical sub types. Recent reports suggest that type 2 diabetes (one of the common chronic diseases worldwide) is linked to the higher incidence, accelerated progression, and aggressiveness of different cancers; especially breast cancer. Breast cancer is hormone-dependent in nature and has a cross-talk with metabolism. A number of antidiabetic therapies are known to exert beneficial effects on various types of cancers, including breast cancer. However, only a few reports are available on the role of incretin-based antidiabetic therapies in cancer as a whole and in breast cancer in particular. The present review sheds light on the potential of incretin based therapies on breast cancer and explores the plausible underlying mechanisms. Additionally, we have also discussed the sub types of breast cancer as well as the intricate relationship between diabetes and breast cancer.
Keywords: sitagliptin